URGENSI DAN JENIS MEDIA PEMBELAJARAN BAHASA ARAB : STUDI ANALISIS TERHADAP AYAT-AYAT AL-QURAN - Rohman, Fadhilah; Yusuf, Ahmad (Sekolah Tinggi Agama Islam (STAI) Al Hidayah Tasikmalaya, 2022)
This paper aims to examine the content of the Qur'anic verse regarding the urgency and types of Arabic language learning media, although it can cover a broad range of scientific disciplines. The research method uses qualitative descriptive analysis. The results show that the urgency of learning media is inspired by the content of the verse about the importance of the Koran (Al-Maidah: 16), it needs to be balanced with the noble behavior of the educator (Al-Ahzab: 31), paying attention to the psychological condition and readiness of students to receive the material (Al-Ahzab: 31). Nahl: 44) and delivered in a structured way (Al-Nahl: 125). The types of Arabic learning media are divided into two major groups, namely material hardware and immaterial hardware. The type of material hardware consists of audio media / al-wasîlah al-sam'iyyah, visual media / al-wasîlah al-bashariyyah and audiovisual media / al-wasîlah al-sam'iyyah-al-bashariyyah. Types of immaterial hardware consist of ideal examples, prohibitions and commands, and rewards and punishments.